Modeling and simulations of metallic and semiconducting single electron transistors - Le Hoang Minh; Dinh Sy Hien (Journal of Technical Education Science, 2017)
Single electron transistor (SET) is a key element in current research area of nanoelectronics which can offer nano-feature size, low power consumption and high operating speed. SET could be promising alternative for MOSFET in the future. The goal of this paper is to discuss about recent advances in fabrication of the SETs and focuses on simulation of their basic quantum device characteristics like tunneling effect, Coulomb blockage, Quantum dot, Coulomb staircase, and Coulomb oscillation. Some results of simulation of two types of metallic and semiconducting SETs have been obtained.